2014 Second International Conference on Advanced Cloud and Big Data 2014
DOI: 10.1109/cbd.2014.24
|View full text |Cite
|
Sign up to set email alerts
|

Energy Consumption Data Based Machine Anomaly Detection

Abstract: Abstract-The ever increasing of product development and the scarcity of the energy resources that those manufacturing activities heavily rely on have made it of great significance the study on how to improve the energy efficiency in manufacturing environment. Energy consumption sensing and collection enables the development of effective solutions to higher energy efficiency. Further, it is found that the data on energy consumption of manufacturing machines also contains the information on the conditions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Through this statistic, it can be shown that the researches of big-data based solutions focus on monitoring, prediction, data analytics and propose ICT solutions in manufacturing in Table 3. [57], [56], [125], Regressions [53], ANN [53], PLM [58], Production ERP MP [63], regression [62], K-means [126] MOM/MES [69], [116], [66], regression [127], Distance, Regression, Selforganizing map, principal component analysis [128], SCADA/DCS/ HMI [129], [71], [104], [130], [131], [104], [132] , [112] Classification [133], OPL [106], KM [134], GA [73], O&M [39], [135] [136], [81], [82], [80] logistic regression, naïve Bayes, and a decision tree [109], regression [137], LSM [138], SVM [83], Anomaly detection [139], DTW [140], RF [141], K-means, Markov [142], KD [24],…”
Section: Applications Of Big Data In Manufacturingmentioning
confidence: 99%
See 2 more Smart Citations
“…Through this statistic, it can be shown that the researches of big-data based solutions focus on monitoring, prediction, data analytics and propose ICT solutions in manufacturing in Table 3. [57], [56], [125], Regressions [53], ANN [53], PLM [58], Production ERP MP [63], regression [62], K-means [126] MOM/MES [69], [116], [66], regression [127], Distance, Regression, Selforganizing map, principal component analysis [128], SCADA/DCS/ HMI [129], [71], [104], [130], [131], [104], [132] , [112] Classification [133], OPL [106], KM [134], GA [73], O&M [39], [135] [136], [81], [82], [80] logistic regression, naïve Bayes, and a decision tree [109], regression [137], LSM [138], SVM [83], Anomaly detection [139], DTW [140], RF [141], K-means, Markov [142], KD [24],…”
Section: Applications Of Big Data In Manufacturingmentioning
confidence: 99%
“…This data is mainly used to predict the long-term performance in production planning [62], global manufacturing network design [94], critical event detection in safety [89]. Both historical batching data and real-time streaming data are integrated to train models and monitor real time condition information such as anomaly detection of machines' energy consumption data [139].…”
Section: Driver 2: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…There is a large body of related research that could be extensively enumerated and discussed [22,23,24,25,26,27]. Most of these approaches show well supported arrangements of bespoke applications integrated to off-the-shelf data management frameworks, standardized file formats and product embedded information devices.…”
Section: Related Workmentioning
confidence: 99%
“…The detection of irregular users through computational intelligence has been treated by many authors with several approaches. The development of intelligent systems has been an alternative and such systems have included techniques as artificial neural networks (ANNs) (Markoč, Hlupić, & Basch, 2011;Zheng, Yang, Niu, Dai, & Zhou, 2018), principle component analysis (PCA) (Singh, Bose, & Joshi, 2017), fuzzy models (Viegas, & Viera, 2017;Nagi et al, 2011), data mining (Chen et al, 2014) and support vector machines (SVMs) (Nagi J. et al, 2010;Pereira et al, 2016).…”
Section: Uparela Gonzalez Jimenez and Quinteromentioning
confidence: 99%